Seismic Resistance Efficiency of RC Building Retrofitted with Fluid Viscous Dampers - Homjaroen, Phetphichit; Hlaing, Hnin Hnin; Sirinipitakul, Terapat; Suwannatrai, Rawirot; Phuchanakit, Tharathep; ไทรงาม, ภาณุมาศ (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
Nowadays, retrofitting existing structures has become a critical aspect of seismic design, particularly because many reinforced concrete (RC) buildings were designed to withstand seismic forces but not in accordance with modern code provisions. Consequently, the existing RC buildings have required retrofitting interventions in order to withstand the effects of seismic action. Therefore, this study investigated the seismic retrofit of an existing RC building using fluid viscous damper (FVD). Moreover, this study investigates the seismic performance of retrofitted structure, focusing on the effectiveness of FVD in mitigating seismic effects. A four-story RC school building in Chiang Rai, Thailand, was selected as the target building, and its seismic performance was analyzed using nonlinear response history analysis (NLRHA). The structural responses before and after retrofitting were compared to evaluate the effectiveness of seismic retrofit with FVD. In this study, the retrofit design procedure and damper distribution were determined using the constant drift method (CD method) to achieve the targeted displacement of 0.5% rad. The results indicate that retrofitted RC structure with FVD significantly reduces the structural drifts to close the target story drift ratio of 0.5% rad., thereby enhancing seismic performance. These findings provide valuable insights into effective seismic retrofit strategies for enhancing the resilience of RC buildings.